OMBUDSMAN- HISTORICAL VIEWS - Hajdari, Enika (European Scientific Journal, ESJ, 2014)
Ombudsman or Mediator represents an institution that more and more is being introduced in different experiences of national institutional organization. This study aims to analyze the operation and the main features of this institution, whose main task is to tear down the wall that separates citizens from public administration. Ombudsman is a mechanism, one of the aspects of democracy that exists for years. Since the period of antiquity, as in Ancient Greece and the Roman Empire also, different institutions can be estimated in current forms of the Ombudsman, because of similar competencies and subjective interests that tutelage against the power of public administration of any time. The institution of Ombudsman in antiquity period has been present under different models and nominations, ranging from the effors, the tribuni plebis up to defensor civitatis. Immediately after completion of this analysis, mainly comparative, we can say that there are no important differences in space and the time at which the Ombudsman has become part of different countries, when we consider his role and main functions, also the modality of interior organization. Since the historical figure of the Swedish Parliamentary Commissioner, today, this institution is generally known as the Protector of Citizens, the bridge between civil society and the administrative apparatus, and every person who sees himself as a victim of an injustice by the Public Administration can be subject of his inquiry. So, the Ombudsman is present in almost all countries, although under different names, like in Spain known as Defensor del Pueblo, in Italy known as Garante, in France, the land of strong republican tradition and centralized known as Médiateur de la République etc…